Polymorphism L26V in the Cathepsin B Gene may be Associated with a Risk of Prostate Cancer and Differentiation - Štiblar-Martinčič, D; Hajdinjak, T (Journal of international medical research, 2009)
Cathepsin B is a lysosomal enzyme thought to be involved in tumour cell invasion and metastasis. This study was designed to investigate the presence of a known leucine to valine mutation at position 26 (L26V) single nucleotide polymorphism (SNP) in the cathepsin B (CTSB) gene in a Slovenian Caucasian population, and to evaluate the association with risk of prostate adenocarcinoma (PCa). A total of 168 PCa patients were compared with 168 controls. There was a significant difference between the frequency of alleles in control subjects and PCa patients: the VV genotype was found in 35.7% of the controls versus 48.8% of the PCa patients. The relative risk for the VV genotype in PCa patients was 1.71. When evaluating the frequency of alleles of the CTSB gene according to tumour grade, increased frequency of the VV genotype was associated with less differentiated tumours. The VV genotype of the CTSB L26V SNP may indicate an increased risk for PCa and less differentiated cancer (higher Gleason score).